2005
DOI: 10.1002/joc.1194
|View full text |Cite
|
Sign up to set email alerts
|

Change in mean temperature as a predictor of extreme temperature change in the Asia–Pacific region

Abstract: Trends (1961Trends ( -2003 in daily maximum and minimum temperatures, extremes and variance were found to be spatially coherent across the Asia-Pacific region. The majority of stations exhibited significant trends: increases in mean maximum and mean minimum temperature, decreases in cold nights and cool days, and increases in warm nights. No station showed a significant increase in cold days or cold nights, but a few sites showed significant decreases in hot days and warm nights. Significant decreases were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
157
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(167 citation statements)
references
References 26 publications
8
157
0
2
Order By: Relevance
“…Klein Tank et al, (2006) used 116 stations located in central and southern Asia to show warming in both the cold and warm tails of the distributions of daily minimum and maximum temperature between 1961 and 2000. Using 91 stations from southeast Asia and the south Pacific, Manton et al, (2001) found significant increases in the annual number of hot days and warm nights, and decreases in cold days and cold nights over 1961-1998. Griffiths et al, (2005 reported similar results for 89 stations across the Asia-Pacific region during 1961-2003. More recently, analyses of changes in climate extremes across South Asia have been described by Sheikh et al, (2010).…”
Section: Introductionmentioning
confidence: 71%
“…Klein Tank et al, (2006) used 116 stations located in central and southern Asia to show warming in both the cold and warm tails of the distributions of daily minimum and maximum temperature between 1961 and 2000. Using 91 stations from southeast Asia and the south Pacific, Manton et al, (2001) found significant increases in the annual number of hot days and warm nights, and decreases in cold days and cold nights over 1961-1998. Griffiths et al, (2005 reported similar results for 89 stations across the Asia-Pacific region during 1961-2003. More recently, analyses of changes in climate extremes across South Asia have been described by Sheikh et al, (2010).…”
Section: Introductionmentioning
confidence: 71%
“…Changes in temperature extremes often scale with changes in the mean 54,55 , indicating local temperature variance has changed little throughout the globe 56 . However, variance in individual climate realizations may change under continued global warming, altering tails of probability distributions and frequencies of extreme events.…”
Section: Extremesmentioning
confidence: 99%
“…Previous observations-based studies have shown warming trends in both average temperatures [e.g., Vose et al, 2005aVose et al, , 2005bLawrimore et al, 2011] and temperature extremes . However, there is conflicting evidence -mostly based on regional analysis -as to whether the response in extremes is simply a result of a shifting mean [e.g., Griffiths et al, 2005;Simolo et al, 2011] or whether changes in other "higher order moments" of the daily temperature are also occurring [Della-Marta et al, 2007;Ballester et al, 2010]. Assessment of the probability distribution of daily temperatures for the globe would help address this question.…”
Section: Introductionmentioning
confidence: 99%